Nâng cao chất lượng in trên các máy in mầu - Đức, Đặng Văn (Journal of Computer Science and Cybernetics, 2016)
This paper describes a method of print quanlity enhencements on the color printers that do not perform true gamma compensation or have no gamma compensation at all. The method has been used in developing HP DeskJet 500 series for PopMap system, a software package developed by Vietnam IOIT for United Nations.